Effects of lysophospholipid supplementation in diets with different oil sources on broiler performance under heat stress - Mohiti-Asli, Maziar; Ghanaatparast-Rashti, Moin; Sharifi, Seyed Davood; Rouhanipour, Hasan; Akbarian, Pooya (Frontiers in Veterinary Science, 2025)
IntroductionFeed cost has gradually increased in poultry production worldwide. One approach to minimizing production cost is dietary manipulation of nutrient supplies through improved feed efficiency. The inclusion of lipids in broiler diets is essential to meet metabolisable energy requirement. This study aimed to investigate the effects of adding lysophospholipids (LP) to diets varying in sources and levels of vegetable oils on growth performance, ileal digestibility of nutrients, and serum lipids of heat-stressed broilers.MethodsA total of 320 Ross 308 broiler chicks were used in a completely randomized design with a 2 × 2 × 2 factorial arrangement of two oil sources (soybean oil; SO, and palm oil; PO), two levels of oil (3 and 6%), and two levels of LP (0 and 100 mg/kg), with four replicates and 10 birds in each replicate. From 28 to 42 days of age, broilers were exposed to 36°C for 5 h everyday.ResultsSupplementation of LP to broilers diet increased BWG from 1 to 21 d of age and for the whole period (p < 0.05). Broilers fed diet containing 6% oil with LP had lower FI from d 22 to 42 d, and better FCR from 22 to 42 d of age and over the entire period (p < 0.05). Apparent ileal digestibility (AID) of EE, and AIDE was higher in diets containing 6% oil than diets with 3% oil (p < 0.05). The AID of EE, and AIDE were higher in broilers fed LP in the diets containing 6% oil (p < 0.05). The LP supplementation to diets reduced serum TG, total cholesterol, and LDL-C, whereas enhanced HDL-C concentrations at 42 d of age (p < 0.05).ConclusionIt was concluded that broilers fed diets containing SO performed better, and LP supplementation enhanced the performance of broilers fed diets containing higher levels of oils.